The Hibiscus Erineum Mite, Aceria hibisci (Acari: Eriophyidae) a New Introduction in the Caribbean and a Potential Threat to Florida's Hibiscus - Cal Welbourn; Jose Carlos Rodrigues; Jorge E. Peña (EDIS)
ENY-852, a 5-page illustrated fact sheet by Cal Welbourn, Jose Carlos Rodrigues, and Jorge E. Peña, describes this mite pest of hibiscus recently confirmed in the Caribbean — symptoms and identification, dispersal, hosts and control. Includes references. Published by the UF Department of Entomology and Nematology, December 2008.